1995
DOI: 10.1128/jcm.33.3.752-754.1995
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric microwell plate hybridization assay for detection of amplified Mycobacterium tuberculosis DNA from sputum samples

Abstract: We developed a colorimetric microwell plate hybridization assay (CoMPHA) for the specific detection of 5-biotinylated amplified Mycobacterium tuberculosis DNA. The optical densities of the CoMPHA corresponded to the initial amounts of purified template DNA. Here, we show that the CoMPHA is useful in distinguishing the PCR-positive and PCR-negative samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…This technique proved to be as sensitive for the detection of amplified products as traditional Southern hybridization but faster and more convenient, because it does not require radioisotopes, as demonstrated for Mycobacterium leprae (33), hepatitis B virus (17), and human immunodeficiency virus type 1 (24). For bacteria, similar techniques have been used to detect different species of Mycobacterium (M. tuberculosis [8,23,37], M. leprae [33], and M. xenopi [13]), as well as Bordetella pertussis (5), Salmonella species (6), C. trachomatis (3), and enterotoxigenic Escherichia coli (28). These studies have shown that colorimetric hybridization is an effective method for routine diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique proved to be as sensitive for the detection of amplified products as traditional Southern hybridization but faster and more convenient, because it does not require radioisotopes, as demonstrated for Mycobacterium leprae (33), hepatitis B virus (17), and human immunodeficiency virus type 1 (24). For bacteria, similar techniques have been used to detect different species of Mycobacterium (M. tuberculosis [8,23,37], M. leprae [33], and M. xenopi [13]), as well as Bordetella pertussis (5), Salmonella species (6), C. trachomatis (3), and enterotoxigenic Escherichia coli (28). These studies have shown that colorimetric hybridization is an effective method for routine diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several investigators have presented sensitive assays for the diagnosis of various viral (16,17,24,30,35), bacterial (3,5,7,8,20,22,23,28,33,37), fungal (14), and protozoal (2) infections on the basis of nonradioactive (colorimetric or chemiluminescent) nucleic acid hybridization. These kinds of techniques are simple, and colorimetry requires only a conventional microtiter spectrophotometric reader and can be readily done on a large scale.…”
mentioning
confidence: 99%
“…The use of PCR to detect the presence of Mycobacterium tuberculosis in clinical specimens has been widely reported (3,6,7,9,15). Although PCR can be specific and sensitive, there are difficulties associated with the technique.…”
mentioning
confidence: 99%
“…These products are captured in a microtiter plate with streptavidincoated wells and detected by hybridization with DIG-labeled oligonucleotide probes. Others have described similar capture assays for the detection of amplicons (3,15,17,18), but these authors did not use a built-in control for inhibition of the PCRs. In our assay, two DIG-labeled oligonucleotide probes are used, permitting detection of amplicons from the M. tuberculosis complex and amplicons from recombinant M. smegmatis 1008 (containing a modified IS6110).…”
Section: Discussionmentioning
confidence: 99%